The Electronic Bracelet Monitoring System in Iraqi Legislation: A Comparative Study - Nasrallah Saad Sayyid Harira, Lect. Dr. Eid (Basra studies journal, 2026)
This research examines the electronic monitoring system using electronic bracelets as an innovative mechanism within Iraqi legislation. It represents one of the newest alternatives to custodial penalties, relying on electronic tracking of offenders outside prison facilities. The significance of electronic bracelet monitoring lies in its prominent role in balancing the interests of individuals and society, given the drawbacks of custodial sentences and the risks associated with mixing offenders. The study addresses key issues in implementing electronic bracelet monitoring, including the effectiveness of supervision, the protection of the monitored individual’s privacy, family acceptance, and the responsiveness of the monitoring authority. The research aims to reduce prison overcrowding resulting from detention or imprisonment, increase the use of consensual alternative sanctions, and facilitate the reintegration of offenders into society. The study concludes with recommendations, the most important of which is the proposal to add Article 294 bis entitled “Execution of Penalties and the Electronic Monitoring System and Custodial Measures”, which grants the court the authority to implement electronic monitoring either at the request of the offender or, in certain cases, by the public prosecutor.